Methods and pitfalls of measuring thermal preference and tolerance in lizards. (August 2017) - Camacho, Agustín; Rusch, Travis W.
Abstract: Understanding methodological and biological sources of bias during the measurement of thermal parameters is essential for the advancement of thermal biology. For more than a century, studies on lizards have deepened our understanding of thermal ecophysiology, employing multiple methods to measure thermal preferences and tolerances. We reviewed 129 articles concerned with measuring preferred body temperature (PBT), voluntary thermal tolerance, and critical temperatures of lizards to offer: a) an overview of the methods used to measure and report these parameters, b) a summary of the methodological and biological factors affecting thermal preference and tolerance, c) recommendations to avoid identified pitfalls, and d) directions for continued progress in our application and understanding of these thermal parameters. We emphasize the need for more methodological and comparative studies. Lastly, we urge researchers to provide more detailed methodological descriptions and suggest ways to make their raw data more informative to increase the utility of thermal biology studies. Highlights: Studies of lizards have been basic for developing thermal biology for at least a century. Still, facts on sources of bias in such studies are scattered across the literature. We reviewed 108 articles, summarize the methods used and point out sources of bias. We found overlooked sources of bias, both methodological and biological. We make recommendations for improving methods in thermal studies of lizards.